INCREASING THE WEAR RESISTANCE OF AGRICULTURAL MACHINERY PARTS WITH COATINGS OF A DISCRETE STRUCTURE. TECHNOLOGICAL SUPPORT OF DISCRETE STRUCTURE COATINGS BY ELECTROSPARK ALLOYING - Shamrai, Vitaliy; Kalinichenko, Vitalii (Problems of Friction and Wear, 2024)
Primed to improve wear resistance, renovation and improvement of parts of the working bodies of agricultural machines by applying coatings of discrete structures using the method of electric spark coating. The advantages of the electric spark alloying process are significant. The results of the stress-strain study of the “stressed surface - coating” composition are presented. To simplify the divisions, a model was developed using an ordered scheme for the distribution of discretes. The dimensions and configuration of the adjacent sections of the coating are established based on minimizing the level of the stress-deformation mill (SDS) with force and temperature influxes on the coating. It is shown that it is necessary to minimize stress-strain The formation of the composition “size surface - coating” is possible by changing the strength and size of discrete pieces on a special surface, as well as the selection of materials for coatings. The proponation method allows, at the design stage, to determine the size of a discrete plot covering the level of excess stress and analyze the influx of their magnitude and sign on the process of cohesive cracking. Discrete coating has much less microstress than when applied with a ball. Coating with tungsten carbide increased the service life of parts by 2.5 times. The hardness of the coating reaches HRC 55...60. When the electrical spark shields of the discrete structure are removed, there is a decrease in the voltage in the same way as the electrical spark shields. The coating of the discrete structure includes a balled coating, which dramatically increases its wear resistance, and the discrete structure of the coating prevents local overstressing, which is the cause of wear of traditional coatings. The design of a discrete coating with optimal matching of geometric parameters makes it possible to ensure the durability of the knives of the harvester’s trimming drum, which work in high-contact grinding and grinding basins. The research results can be used in the development of technological processes for the formation of electric spark coatings of a discrete structure in the production, development and updating of working bodies and parts of agricultural machines and equipment in general, by improving wear resistance and service life.